Desenvolvimento de sistema de acesso a ambientes usando RFID e Bluetooth - Eri, Luiz Fernando Hidechiro (2021)
This work presents a model of an access system to environments using RFID technology, linked to the sending of data to an Android platform application via Bluetooth that aims to increase the security of the process. Given the importance of object connectivity to the internet, it is necessary to carry out this project in order to obtain an access system solution, using RFID and the creation of an application via MIT App Inventor. For the creation of this project, the materials used were Arduino Uno, Bluetooth HC-05 and the RFID module. The application has the function of registering and deleting users, in addition to viewing information such as the date and time of users who used the system. In addition, the application does not authorize the registration of two cards at the same time, generating a block for possible attacks. The system, being a prototype, can perform all the functions provided and it is possible to use it in several places, requiring only the identification of the user.